Answer:
20
Step-by-step explanation:
Answer:
.
Step-by-step explanation:
We have been given an equation
. We are supposed to solve our given equation step by step.
Step 1: Use the distributive property.
![3\cdot 2x+3\cdot 6-4x=2\cdot 5x-2\cdot 2+6](https://tex.z-dn.net/?f=3%5Ccdot%202x%2B3%5Ccdot%206-4x%3D2%5Ccdot%205x-2%5Ccdot%202%2B6)
![6x+18-4x=10x-4+6](https://tex.z-dn.net/?f=6x%2B18-4x%3D10x-4%2B6)
Step 2: Combine like terms.
![6x-4x+18=10x-4+6](https://tex.z-dn.net/?f=6x-4x%2B18%3D10x-4%2B6)
![2x+18=10x+2](https://tex.z-dn.net/?f=2x%2B18%3D10x%2B2)
Step 3: Use subtraction property of equality:
![2x-2x+18-2=10x-2x+2-2](https://tex.z-dn.net/?f=2x-2x%2B18-2%3D10x-2x%2B2-2)
![16=8x](https://tex.z-dn.net/?f=16%3D8x)
Step 4: Use the division property of equality:
![\frac{16}{8}=\frac{8x}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B16%7D%7B8%7D%3D%5Cfrac%7B8x%7D%7B8%7D)
![2=x](https://tex.z-dn.net/?f=2%3Dx)
Therefore, the solution of our given equation is
.
The slope is 0 and the y-intercept is (0,18)
Answer:
wait of a ?
Step-by-step explanation: